2005
DOI: 10.1111/j.1445-2197.2005.03367.x
|View full text |Cite
|
Sign up to set email alerts
|

Hartmann Procedure: Is It Still Relevant Today?

Abstract: Though the idea of primary anastomosis with on table lavage for left sided anastomosis seems attractive, we think the Hartmann procedure is still useful for selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
41
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 29 publications
(28 reference statements)
7
41
1
3
Order By: Relevance
“…In our material, intestinal continuity after the Hartmann procedure was restored only in 10.2% of patients. A similarly low rate of restoration (0-35%) has been reported by other authors (6,7,12). It probably results from the fact that postoperative and postradiation changes in the pelvis minor preclude safe dissection of the rectal stump and its preparation for anastomosis.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In our material, intestinal continuity after the Hartmann procedure was restored only in 10.2% of patients. A similarly low rate of restoration (0-35%) has been reported by other authors (6,7,12). It probably results from the fact that postoperative and postradiation changes in the pelvis minor preclude safe dissection of the rectal stump and its preparation for anastomosis.…”
Section: Discussionmentioning
confidence: 63%
“…Local resection of rectal cancer, especially with the use of the TEM technique (transanal endoscopic microsurgery) gives good functional results and entails low risk of complications, but indications for local resection are limited to a strictly selected, and thus sparse, group of patients with early stage tumour (1)(2)(3)(4)(5). The rate of reconstructive surgeries after the Hartmann procedure in patients with rectal cancer is low (6,7). The best chance for maintaining intestinal continuity can be seen in the anterior resection, which, however, entails the risk of leak from a lowlying anastomosis, which can necessitate reoperation and formation of a permanent colostomy.…”
mentioning
confidence: 99%
“…Nevertheless, many others have concluded that immunosuppression, septic shock, fecal peritonitis, or high cardiac risk patients at admission were correlated with higher morbidity and mortality rates, and that usage of a two-stage procedure with or without primary anastomosis would be safer than one-stage surgery. [1,5,16,18] There is no comment about the timing of the second stage of the operation, but most of the authors favor delaying the second stage, usually preferring to perform it 6 months after the first stage. [14,18] In conclusion, colon perforation due to immunoUnexpected colonic perforation in a renal recipient Ulus Travma Acil Cerrahi Derg suppressant use in renal allograft recipients is a rare but serious complication, with high mortality and morbidity rates.…”
Section: Discussionmentioning
confidence: 99%
“…[1,5,16,18] There is no comment about the timing of the second stage of the operation, but most of the authors favor delaying the second stage, usually preferring to perform it 6 months after the first stage. [14,18] In conclusion, colon perforation due to immunoUnexpected colonic perforation in a renal recipient Ulus Travma Acil Cerrahi Derg suppressant use in renal allograft recipients is a rare but serious complication, with high mortality and morbidity rates. It must be diagnosed early and treated aggressively.…”
Section: Discussionmentioning
confidence: 99%
“…Dieses Konzept wird derzeit aufgrund zahlreicher Gründe hinterfragt. Die skizzierte Hartmann-Prozedur hat eine hohe perioperative Morbidität um 40% und eine Mortalität von bis zu 20% [33,34]; des Weiteren besteht eine sehr geringe Rate an Kontinuitätswiederherstellung von unter 40%. Liang et al [35] haben in einer erst kürzlich publizierten Arbeit von ihren Erfahrungen mit zwei laparoskopischen Behandlungsstrategien - laparoskopische Lavage und Drainage sowie laparoskopische Hartmann-Operation - für die perforierte Sigmadivertikulitis berichtet.…”
Section: Spezielles Vorgehen Bei Bestimmten Krankheitsbildernunclassified